2011
DOI: 10.1152/jn.00154.2010
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Storage Contribution to Vestibular Self-Motion Perception in Healthy Human Subjects

Abstract: Self-motion perception after a sudden stop from a sustained rotation in darkness lasts approximately as long as reflexive eye movements. We hypothesized that, after an angular velocity step, self-motion perception and reflexive eye movements are driven by the same vestibular pathways. In 16 healthy subjects (25-71 years of age), perceived rotational velocity (PRV) and the vestibulo-ocular reflex (rVOR) after sudden decelerations (90°/s(2)) from constant-velocity (90°/s) earth-vertical axis rotations were simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 74 publications
7
73
2
Order By: Relevance
“…When considered in the context of other modes of sensory perception, this finding is not surprising. But in the context of previous studies of yaw rotation perception that have focused on long duration stimuli in which velocity storage is predominant (Keller and Henn 1984;Sinha et al 2008;Bertolini et al 2011;Bertolini et al 2012), these findings may be unexpected. The reason aftereffects were not found in the previous studies was likely because the duration of stimuli was relatively long (i.e., on the order of minutes) a time course where velocity storage may be predominant.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…When considered in the context of other modes of sensory perception, this finding is not surprising. But in the context of previous studies of yaw rotation perception that have focused on long duration stimuli in which velocity storage is predominant (Keller and Henn 1984;Sinha et al 2008;Bertolini et al 2011;Bertolini et al 2012), these findings may be unexpected. The reason aftereffects were not found in the previous studies was likely because the duration of stimuli was relatively long (i.e., on the order of minutes) a time course where velocity storage may be predominant.…”
Section: Discussionmentioning
confidence: 78%
“…For this reason, there is usually negative feedback built into the central velocity storage loop. To stimulate this, G i is set to −1/15 s, a value previously found to fit vestibular perception after long duration rotation (Bertolini et al 2011) and identified as a typical value in a recent review (Laurens and Angelaki 2011). However, this velocity storage model did not predict the current observations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations